Revisiting the role of Akkermansia muciniphila as a therapeutic bacterium - Jiyeon Si; Hyena Kang; Hyun Ju You; GwangPyo Ko (Gut Microbes)
Despite a short history since its first isolation, Akkermansia muciniphila has been extensively studied in relation to its effects on human metabolism. A recent human intervention study also demonstrated that the bacterium is safe to use for therapeutic purposes. The best-known effects of A. muciniphila in human health and disease relate to its ability to strengthen gut integrity, modulate insulin resistance, and protect the host from metabolic inflammation. A further molecular mechanism, induction of GLP-1 secretion through ICAM-2 receptor, was recently discovered with the identification of a new bacterial protein produced by A. muciniphila. However, other studies have suggested a detrimental role for A. muciniphila in specific host immune settings. Here, we evaluate the molecular, mechanistic effects of A. muciniphila in host health and suggest some of the missing links to be connected before the organism should be considered as a next-generation biotherapeutic agent.